Analisis Yuridis Tindak Pidana Penggelapan berdasarkan Pasal 372 Kitab Undang-Undang Hukum Pidana: Studi Kasus Perkara No. 16/Pid.B/2022/Pn.Pti - Silalahi, DI.; Khamim, Khamim (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2024)
The main requirement for an act to be considered a criminal offense is the existence of a rule that prohibits it and is punishable by law for anyone who violates it, with one of the rules contained in the Criminal Code. Criminal liability can occur when there is an error caused by intention, negligence, and the absence of a forgiving reason. In certain offenses, criminal liability can occur before the actual criminal act takes place and the act committed is a realization of part of the criminal liability. An example of the issue is when initially the intention is not categorized as a crime but it can become a crime if the intention changes, such as when we borrow or rent an item to someone for a few days, but on the last day the borrower changes their intention to keep the item. In that case, it can be categorized as embezzlement as in Case No. 16/Pid.B/2022/PN.Pti.